The effects of sexuality education program on sexual quality of life among patients following coronary artery bypass graft - Arthit Oeychanai; Thitipong Tankumpuan; Napaporn Wanitkun; Teerapong Tocharoenchok (Scientific Reports)
Abstract Patients who undergo coronary artery bypass grafting surgery rarely receive information or have discussions regarding sexual quality of life with their healthcare providers. This quasi-experimental study aimed to assess the effectiveness of sexuality education programs on sexual quality of life following coronary artery bypass grafting surgery in Thailand. The experimental group, consisting of 30 participants, received sexual education, while a control group of 30 participants received routine care. The primary outcome measured was sexual quality of life, evaluated both before and after the intervention. An independent samples t-test was utilized to compare outcomes between the two groups, and a paired t-test was employed to assess changes within the intervention group. The results demonstrated a statistically significant difference in sexual quality of life between the groups (t = 3.47, p = 0.001). Moreover, the sexual quality of life score increased significantly in the intervention group (t = 4.52, p < 0.001), while no significant changes were observed in the control group (t = 0.41, p = 0.688). These findings underscore the positive impact of sexuality education programs on improving sexual quality of life following coronary artery bypass grafting. It is essential for healthcare providers to incorporate health education for patients prior to hospital discharge and to monitor sexual quality of life during follow-up visits.